Brain abscesses in a patient with a patent foramen ovale: a case report - Jan, Fuad (BioMed Central, 2009)
INTRODUCTION: Brain abscesses arising from right-to-left cardiac shunting are very rare in adults. CASE PRESENTATION: We describe the case of a 47-year-old non-hispanic white male with periodontal disease who developed several brain abscesses caused by Streptococcus intermedius. A comprehensive workup revealed a patent foramen ovale with oral flora as the only plausible explanation for the brain abscesses. CONCLUSION: Based on this case and the relevant literature, we suggest an association between a silent patent foramen ovale, paradoxical microbial dissemination to the brain, and the development of brain abscesses.